PENERAPAN PROGRAM DIGITALISASI PADA UMKM MELALUI WHATSAPP BISNIS DAN PEMBAYARAN DENGAN QRIS DI DESA SIRNAJATI - Alfiyyani, Eka Farras; Berry, Yunike; Marginingsih, Ria (An-Nizam, 2024)
Advances in technology provide the potential for business people to promote their products or services, and in the current economic situation, the appropriate strategy is digital marketing. WhatsApp Business allows MSMEs to interact with customers directly, promote products or services, and accept orders through the platform. QRIS (Quick Response Code Indonesian Standard) is a QR code standard used for digital payment transactions in Indonesia. WhatsApp Business and QRIS were chosen because these two technologies have great potential in increasing the efficiency and accessibility of MSMEs in doing business digitally. Therefore, my goal is to create a digital-based MSME program through sales with WhatsApp Business and creating a digital payment method with QRIS in Sirnajati Village. Sirnajati Village was chosen as the Program location because it is representative as an illustration of MSMEs in rural areas that have the potential to be developed through the use of digital technology. The method for implementing this program is based on a participatory approach, which involves collaboration between the local government, MSME actors, and the Sirnajati Village community. From this program I hope to increase knowledge about digital development and methods that can be applied for online marketing in Sirnajati Village